Cholesterol and Linoleic Acid: a forgotten cooperation? Cholesterol: is still a negative myth? - Cocchi, Massimo; Minuto, Chiara (Progress in Nutrition, 2020)
This mini review proposes a reflection on the role of cholesterol in its cooperation with oxygen andlinoleic acid. The authors deal with the logics of membrane mobility, where the concentrations of cholesteroland linoleic acid exert a strong influence on the dynamics of the greater or lesser entry of oxygen and, therefore,on the impact in the determinism of oxidative phenomena.